Anchoring Ionic Liquid in Copper Electrocatalyst for Improving CO2 Conversion to Ethylene. (9th February 2022) - Sha, Yufei; Zhang, Jianling; Cheng, Xiuyan; Xu, Mingzhao; Su, Zhuizhui; Wang, Yanyue; Hu, Jingyang; Han, Buxing; Zheng, Lirong
Abstract: Electrochemical conversion of CO2 to valuable fuels is appealing for CO2 fixation and energy storage. The Cu‐based catalysts feature unique superiorities, but achieving high ethylene selectivity is still restricted. In this study, we propose the anchoring of an ionic liquid (IL) on a Cu electrocatalyst for improving the electrochemical CO2 reduction to ethylene. In a water‐based electrolyte and a commonly used H‐type cell, a high ethylene Faradaic efficiency of 77.3 % was achieved at −1.49 V (vs. RHE). Experimental and theoretical studies reveal that an IL can modify the electronic structure of a Cu catalyst through its interaction with Cu, making it more conducive to *CO dimerization for ethylene formation. Abstract : The ionic liquid 1‐butyl‐3‐methylimidazolium nitrate (BmimNO3 ) was anchored into Cu, through which the atomic coordination and electronic properties of Cu can be optimized to facilitate C−C coupling. This electrocatalyst can reduce CO2 to C2 H4 with high selectivity. The Faradaic efficiency of C2 H4 reaches 77.3 % at −1.49 V (vs. RHE) in KHCO3 aqueous solution using a H‐type cell, much higher than that over pure Cu catalyst (31.2 %).